2021
DOI: 10.1021/acscatal.0c04627
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Zinc on Bimetallic Fe5C2–ZnO Catalysts for Highly Selective Carbon Dioxide Hydrogenation to High Carbon α-Olefins

Abstract: In this work, Fe−Zn catalysts were prepared, characterized, and examined for the synthesis of linear high carbon α-olefins (LAOs; C ≥ 4) directly from CO 2 hydrogenation. The relationship of performance and structure has been established to unravel the role of ZnO in bimetallic Fe 5 C 2 −ZnO catalysts. A Fe2Zn1 catalyst showed high selectivity to C 2 −C 7 olefins (a selectivity of 57.8% in gas phase) after 200 h of time-on-stream and total C 4+ olefins selectivity in liquid products of 81.9% with 85.9% LAOs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 89 publications
4
33
0
1
Order By: Relevance
“…488 kOe for A site and 456 kOe for B site). 33,51 This happens because of the replacement of Fe 2+ by Zn 2+ and Fe 3+ by Al 3+ and a similar variation has been observed on the spinel system Zn x Co 1−x Fe 2−x Al x O 4 . 52 The XPS results of the spent catalysts are shown in Figure 4a, and the binding energies (BE) of the detected peaks and the surface atomic concentrations are given in Table S6.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…488 kOe for A site and 456 kOe for B site). 33,51 This happens because of the replacement of Fe 2+ by Zn 2+ and Fe 3+ by Al 3+ and a similar variation has been observed on the spinel system Zn x Co 1−x Fe 2−x Al x O 4 . 52 The XPS results of the spent catalysts are shown in Figure 4a, and the binding energies (BE) of the detected peaks and the surface atomic concentrations are given in Table S6.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
“…32 Recently, by studying the phase transformation during activation and reaction, our group revealed the stabilization effects of Zn on the active phase of Fe x C during CO 2 hydrogenation. 33 At present, however, studies on the effect of different additives on Fe-based catalysts are mostly isolated even though multiple combinations of mix additives have been employed in industrial catalysts. 34,35 Xu et al recently unveiled a subtle synergy between Na and Mn in Fe-based catalysts in CO 2 hydrogenation as Na mediates the strong interaction between Fe and Mn.…”
Section: ■ Introductionmentioning
confidence: 99%
“…That is, the ability to catalyze C 2+ production ranks as Fe 5 C 2 > Fe 3 C >> Fe 3 O 4 . Density functional theory (DFT) investigations showed that CO 2 activation is more facile on Fe 5 C 2 and Fe 3 C than on Fe 3 O 4 (45,46), and Han and colleagues (27,39) found that the transition of Fe 5 C 2 to Fe 3 O 4 causes the deactivation in CO 2 hydrogenation. From the comparison on the performance over model catalysts and Fe NPs with different TOS (Fig.…”
Section: Surface Structurementioning
confidence: 99%
“…), hydrogenating CO 2 via thermo-catalysis can not only mitigate CO 2 emissions, but also effective in providing valuable organic chemicals. [5,6] Significant progress has been made in the selective catalytic hydrogenation of CO 2 into C 2 + hydrocarbons (e. g., olefins, [7][8][9][10][11][12] isoparaffins, [13] and aromatics [14][15][16][17][18] and oxygenates (e. g., methanol [19,20] and ethanol [21] ). Among these products, olefins are basic feedstocks for the production of various important commodities.…”
Section: Introductionmentioning
confidence: 99%